Inspecting Histamine Isolated from Fish through a Highly Selective Molecularly Imprinted Electrochemical Sensor Approach - Muhammad Abdurrahman, Munir; Fitria, Rahmawati; Jamia Azdina, Jamal; Sofian, Ibrahim; Mazlina, Mohd Said; Mohamad Syahrizal, Ahmad (American Chemical Society, 2023)
Numerous analytical approaches have been developed to determine histamine levels in food samples due to its health consequences. Consuming histamine over the Food and Drug Administration (FDA)-regulated 50 mg kg–1 limit would result in chronic toxicity. Consequently, the present study discusses a novel electrochemical approach to evaluate histamine levels in fish products via a molecularly imprinted polymer (MIP) on an electrode surface. The film was produced with electropolymerized polyurethane (PU), which maintained the histamine compound. Fourier-transform infrared (FTIR) spectroscopy was applied to verify the MIP manufactured in this study. The capability of the polymer was measured by assessing its electron shifts with cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). Differential pulse voltammetry (DPV) was also employed to validate the sensing method. The MIP/screen-printed electrode (SPE) and non-imprinted polymer (NIP)/SPE recorded a linear response ranging from 1 to 1000 nmol L–1 at the 1.765 and 709 nmol L–1 detection limits. The sensing technique was subsequently utilized to determine the histamine levels in selected samples at room temperature (25 °C). Generally, the sensor allowed the accurate and precise detection of histamine in the fish samples. Furthermore, the approach could be categorized as a simple technique that is low-cost and suitable for on-site detections.